Epidemiological characteristics and influencing factors of the cluster outbreaks of influenza-like illness in Yangpu District， Shanghai， 2012‒2022 - XIE Qianru; JIANG Chenyan; TAO Fangfang; QIAO Peng (Shanghai yufang yixue, 2025)
ObjectiveTo analyze the epidemiological characteristics and influencing factors of clustered influenza-like illness (ILI) outbreaks in Yangpu District, Shanghai from 2012 to 2022, and to provide a scientific basis for formulating specific prevention and control measures of influenza in this district.MethodsData on clustered ILI outbreaks from 2012 to 2022 were collected, and the epidemiological pattern of the cluster outbreaks of influenza and its influencing factors of prevalence and duration were explored using statistical methods such as descriptive epidemiology, χ² test and logistic regression analysis.ResultsA total of 60 clustered ILI outbreaks were reported in Yangpu District, Shanghai from 2012 to 2022, with a cumulative number of 543 cases and an annual average incidence rate of 16.96%. The male-to-female ratio was 1.06∶1. The largest number of ILI were reported in 2019, mainly from November to January of the next year, with December being the peak of outbreaks. The Streets of Changhai Rd. in Yangpu District had the largest number of reported outbreaks, accounting for 30.00% of the total outbreaks. Influenza cluster outbreaks occurred in schools, with the majority of outbreaks and cases reported in primary schools (accounting for 65.00% and 62.06% of the total, respectively). The outbreaks were mainly caused by influenza B virus, accounting for 50% of the total number of outbreaks. The prevalence rate of influenza cluster outbreaks varied among different schools in terms of their affiliated streets, school attributes and school types, with those in Kongjiang Rd. Subdistrict, private schools, and childcare institutions being relatively high. The duration of outbreaks reported for >2 days was longer than those reported for ≤2 days (OR=8.604, 95%CI: 1.509–49.067).ConclusionThe ILI outbreaks in Yangpu District present a seasonal pattern, with primary schools and Changhai Rd. Street as the targeted places for implementing prevention and control measures. Timely detection and reporting and active disposal can prevent a further spread of the outbreaks.